THE INFLUENCE OF SERVICE QUALITY AND PRODUCT QUALITY ON CUSTOMER SATISFACTION AT PT. AIRMAS PERKASA - Reza Khairul Hadi; Asep Sulaeman; Komarudin Komarudin (International Journal Management and Economic, 2025)
This study aims to analyze the impact of service quality and product quality on customer satisfaction at PT. Airmas Perkasa, a provider of information technology hardware in Jakarta. The study uses a quantitative approach with a survey method, involving 98 respondents. Service quality is measured based on dimensions of reliability, responsiveness, assurance, empathy, and tangible evidence, while product quality is assessed through performance, features, durability, and product reliability. Customer satisfaction is measured through consumer evaluations of the products and services received. The analysis results show that service quality has a significant impact on customer satisfaction. Product quality also significantly affects customer satisfaction. Simultaneously, service quality and product quality have a significant impact on customer satisfaction, with an F-value of 289.216 and an R² of 0.859, indicating that both variables together explain 85.9% of the variation in customer satisfaction. The study concludes that improving both service quality and product quality can significantly enhance customer satisfaction. PT. Airmas Perkasa is advised to continue improving its services and products to maintain customer satisfaction and strengthen its competitive edge in the market.